Exploring edge functionalised blue phosphorene nanoribbons as novel photocatalysts for water splitting - Maibam, Ashakiran; Chakraborty, Debalina; Joshi, Krati; Krishnamurty, Sailaja (New Journal of Chemistry, 2021)
Hydrogen gas, a highly combustible and eco-friendly fuel is stealing the limelight and its production is one of the major areas of research. An efficient and green method for producing clean hydrogen gas with no harmful by-product is water splitting. With the introduction of low dimensional materials, water splitting has become an easier and cost-effective process. The present work demonstrates the application of one such low dimensional material viz., edge functionalised Blue Phosphorene Nano-Ribbons (BPNRs) as potential photocatalysts. With a carrier mobility of 10(3) cm(2) V-1 s(-1) and a band gap of 1.5-3.0 eV, BPNRs are an attractive candidate for photocatalysis. BPNRs with different edge oreintations, viz. zigzag and armchair are functionalised with CH3O, COOCH3, CHO, COOH, OH, NH2, CONH2, SH, C6H5, and NO2 groups. Their performance towards activating water molecules at different sites on the nanoribbon is studied. The functionalised edges of the BPNRs are the active sites showing similar to 1.2% to 3.2% efficiency in activating the O-H bond of the water molecule. Among the different groups explored, CONH2 functionalised zigzag BPNR clearly exhibits a higher potential towards the adsorption of water molecules (-0.98 eV) and activation of O-H bonds with an elongation of 3.2% and a red shift of 500.6 cm(-1). This is attributed to the lone pair of electrons on the nitrogen atom contributing to the electron donating nature of the CONH2 functional group.